Ask : the counterintuitive online formula to discover exactly what your customers want to buy ... create a mass of raving fans ... and take any business to the next level - Levesque, Ryan ([Nashville, TN] : Dunham Books, 2015)
When it comes to the way business is carried out online, the earth beneath our feet is shifting right now--and shifting quickly. The one-size-fits-all approach is fast becoming obsolete. More and more businesses are learning that the more they tailor-make the messages they put on their sites, as well as how they interact with every single user, the more satisfied customers get--and the more they earn.
Pt. 1. Ask: the story. You: who, what, & why -- Strange questions ... and strange answers -- The discovery -- My crisis -- Working hard for the dream -- An unexpected twist -- The letter -- Standing on the shoulders of giants -- Taking the leap -- Things finally come together -- pt. 2. Ask: the methodology. Getting started: how to read the Ask formula methodology -- The process: prepare, persuade, segment, prescrie, profit, pivot -- Prepare: the deep dive survey -- Persuade: the prospect self-discovery landing page -- Segment: the micro-commitment bucket survey -- Prescribe: the post-survey sales prescription -- Profit: the profit maximization upsell sequence -- Pivot: the email follow-up feedback loop -- Case study #1: tennis training, zero to $250,000 in 6 months -- Case study #2: water ionizer market, $750,000 in 5 days -- Why: the reason for writing this book -- Next steps: now it's your turn to Ask.
Keywords: Internet marketing; Direct marketing; Social media